Alef, mem, tau : kabbalistic musings on time, truth, and death - Wolfson, Elliot R. (Taubman lectures in Jewish studies ;, 2006)
This highly original, provocative, and poetic work explores the nexus of time, truth, and death in the symbolic world of medieval kabbalah.